Pengaruh Pupuk Organik Cair Dari Limbah Tahu Terhadap Pertumbuhan Benih Jagung Di Desa Kencong Kabupaten Jember - Vikky Pramudya Herdiansyah Poeloengan; Lutfi Diah Mufida; Dwi Wahyuningtyas; Faris Sahrur Rohman; Ida Nur Hidayah; Pedro Renardo Naibaho; Riska Ayu Pratama; Deven Agni Pratama (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2024)
The tofu making process produces solid waste and liquid waste. Most of the liquid waste is disposed of directly into the river causing pollution to the river and other water sources. Therefore tofu liquid waste processing is needed to reduce environmental pollution and benefit the wider community, one of which is by utilizing tofu liquid waste into liquid organic fertilizer by fermentation. The fermentation process takes 15 days with the addition of EM4, rumen, sugar solution, and water. All ingredients are mixed and put into a closed container. This activity was carried out in Ponjen Hamlet, Kencong Village. This activity involved KKN student and farmer group. The forms of activities carried out were visits to the Ponjen Hamlet farmer group, conducting interviews, observations, fertilizer making practices, observing corn seeds, data processing, and drawing conclusions.